Práticas de leitura : lembranças de família e histórias de vida - Santos, Marluce de Souza Lopes (2016)
The objective of this study is to investigate the reading practices of eight women from different generations belonging to my family. Is part of the area of studies on the History of Education, with the theoretical support of Cultural History and methodology of Oral History. It is a bibliographical and documentary research that has an autobiographical approach, using the concepts of appropriation, representations and practices with a view to Roger Chartier, to understand the different interpretations and different uses people make of the texts they read. This research adopt the views of Michael Pollack, Ecléa Bosi and Maurice Halbwachs, regarding the concept of memory. The sources used are statements taken from semi-structured interviews, in order to verify, in the vestiges of the past, everyday strokes experienced by interviewees in the relationship established with environments favorable to the constitution of each one as readers. It is hoped that this study to better understand the relationship between reading practices, family education and schooling.